If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(7x + -9) = 70 Reorder the terms: 3x + -2(-9 + 7x) = 70 3x + (-9 * -2 + 7x * -2) = 70 3x + (18 + -14x) = 70 Reorder the terms: 18 + 3x + -14x = 70 Combine like terms: 3x + -14x = -11x 18 + -11x = 70 Solving 18 + -11x = 70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -11x = 70 + -18 Combine like terms: 18 + -18 = 0 0 + -11x = 70 + -18 -11x = 70 + -18 Combine like terms: 70 + -18 = 52 -11x = 52 Divide each side by '-11'. x = -4.727272727 Simplifying x = -4.727272727
| 9(t-6)6+5t=7(2t+3)-10 | | 39/b=13/15 | | -2x=-4+2x | | 11(7+b)=-33 | | 960/4 | | 960/4 | | 7xsquared=-12 | | 0=-5/3x-9 | | 2/2f | | (x^2+7x+12)x+5=y | | 5/36.25=8 | | 4x-y+1=180 | | 5-1/2z=3/4 | | -19+9= | | 64+32+a=180 | | 6.89p+x=5 | | 1/3x+2=3/4 | | x/-12=-3 | | x^3+5x^2+10x=2 | | 3(4x-4)=(12x-1) | | 9=2y+3(y+8) | | 1/x2-1=0 | | x/y=8 | | 15/(2/3) | | 0.14x+29.95=.39x+4.95 | | 3x=-y-t | | 90+5f+2+122=180 | | 6(n+7)=7n-4 | | 4x^2-15x=-3x^2-2x-6 | | 8x+22y=10 | | 3-9(4x+12)=6(4x+24-12) | | 3-9(4x+12)=6(4x+24-12) |